Effect of carrageenans on vegetable jelly in humans with hypercholesterolemia - Valado, Ana (2020)
Submitted by Maria Loureiro (maria.loureiro@estescoimbra.pt) on 2020-02-20T11:18:04Z No. of bitstreams: 1 artigo gelatina 2020.pdf: 601331 bytes, checksum: 5e0505872df72b40834c7ebdf05bb5fc (MD5)